2015
DOI: 10.31018/jans.v7i1.621
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for climate change impacts on irrigated crops in National Capital Region of India

Abstract: Irrigation has helped in increasing food production and achieving food security in India. However, climate change is expected to affect the crop production in irrigated area particularly in groundwater irrigated areas. This study was undertaken for suggesting strategies to climate change impact on irrigated crops based on projected change in crop water requirement and groundwater availability for irrigation in the National Capital Territory of Delhi. Prevailing groundwater recharge in the study area during mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The total ETc of across all locations was shown to be variations as the climate changes under all scenarios. In addition to these, similar kind of results also observed in [14]. [16] anticipate a rise in global ETc in all places, as predicted by the INCCA and IPCC [17].…”
Section: Predicted Crop Water Requirement (Etc)supporting
confidence: 86%
See 1 more Smart Citation
“…The total ETc of across all locations was shown to be variations as the climate changes under all scenarios. In addition to these, similar kind of results also observed in [14]. [16] anticipate a rise in global ETc in all places, as predicted by the INCCA and IPCC [17].…”
Section: Predicted Crop Water Requirement (Etc)supporting
confidence: 86%
“…According to the findings, there has been a decline in ETc's Shahapur and Shorapur, and an increase in ETc of Yadgir during the last 35 years. In addition, the wind speed, relative humidity, and solar radiation changes had an impact on the increase of crop water requirement [14]. The study region is comprised of black dirt and some measure of red soil.…”
Section: Crop Water Requirement (Et C )mentioning
confidence: 99%
“…Based on water requirement under various climate change scenarios, appropriate strategies to cope up the climate change impact on rabi crops needs to be planned. Rainwater harvesting and artificial groundwater recharge need to be made mandatory in the study area for increasing the groundwater recharge and water availability (Kambale et al, 2015). It is concluded that in order to ensure long-term and sustainable groundwater utilization in the region, proper estimation of crop water requirement and optimal water management are needed.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to more vigorous hydrologic cycle, influences precipitation, its intensities, frequencies, extreme events and changes in soil moisture status (Srinivasarao et al, 2014). Many studies reported that irrigated agriculture would be severely affected by climate change due to increased crop water requirement and decreased water resources availability especially in the arid and semiarid regions of world including India (Mahmood, 1997;Goyal, 2004;De Silva et al, 2007;INCCA, 2010;Shahid, 2011;Kambale et al, 2015;Srinivasarao et al, 2015;Behera et al, 2016;Srinivasarao et al, 2016b). Longer drought periods, considered to be the expected impact of climate change, increases the water stress in crops and reduces the growing period and crop productivity (IFPRI, 2009;Manekar and Bharadiya, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation